Meso cracking mechanism of ice saturated cross fissured sandstone under dynamic loading - Tianzuo Huang; Linxin Wang; Yuan Chang (Scientific Reports)
Abstract Cross-fissures filled with ice are common in the rock masses of mine slopes in cold plateau regions. The mechanical response of these cracks under near-field dynamic loads, such as blasting, significantly affects slope stability. This paper conducted drop hammer tests on four ice-saturated cross-fissured sandstones with different angles, and the cracking mechanism analyzed using PFC2D numerical simulation. The results show that strain-time history curve can be divided into four stages: compaction, elastic deformation, crack propagation, and complete failure. The macroscopic failure mode of the rock samples is primarily tensile. Cracks typically extending from the loading end to the bottom of the rock sample. Horizontal cracks primarily result in shear cracks, whereas non-horizontal cracks predominantly exhibit tensile cracks. When the crack angle is 45°, the crack initiation stress is greater than 30° and 60°. The damage stress exhibits a pattern of initially decreasing and then increasing with an increase in fissure angles. These findings offer valuable insights for optimizing mine slope stability in cold plateau regions, particularly when designing measures to mitigate the effects of dynamic loads on rock masses with ice-filled fissures.